The Effect Of Giving Green Tea (Camellia Sinensis L.) on Leukocyte Counts of Smokers - Novilla, Arina; Wasdili, Fini Ainun Qolbi; Suseno, Novalia Rachma (Fakultas Kedokteran, 2024)
Background: Cigarette smoke consists of the main smoke (main stream) which contains 25% levels of hazardous materials and side streams which contain 75% levels of hazardous materials. Cigarette smoke contains more than 4000 harmful chemicals, including nicotine, tar, lead, carbon monoxide (CO) and various other free radicals which are carcinogenic. Each puff of cigarette smoke contains 1015 oxidative free radicals which are the main source of oxidative stress which has the potential as a mediator of endothelial dysfunction, increased blood thrombogeneity, and inflammatory response. Someone who smokes continuously for a long time is known to have a leukocyte count 20-25% higher than people who don't smoke. It is known that the entry of nicotine into the body causes leukocytosis due to the circulation of catecholamines due to the increase in hormones such as epinephrine and cortisol by nicotine. Objective: Seeing the leukocyte count values in smokers who consume green tea (Camellia sinensis L). Methods : This research method uses descriptive method. The research samples were taken from active smokers in the Unjani FITKES environment as many as 28 samples. Data collection was carried out by filling out questionnaires and consent forms. Then an examination of the leukocyte count was carried out including the value of eosinophils, segment neutrophils, stem neutrophils, lymphocytes and monocytes. Data analysis is reported as a percentage. Results : Based on the results of the study, the sig value for eosinophils was (0.191), segment neutrophils (0.876), stem neutrophils (0.080), lymphocytes (0.333) and monocytes were smaller (0.003). it can be concluded that green tea has an effect but not significant on the leukocyte count value to neutralize free radicals caused by smoking. Conclusion : Based on this study, it was concluded that from 28 samples of active smokers, it was found that 17 people (60.7%) had an increase in monocytes. It can be concluded that green tea has an effect, but not significantly, on the leukocyte count value to neutralize free radicals caused by smoking.